PENGARUH MODEL PEMBELAJARAN INKUIRI BERBANTUAN MEDIA GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS X - Nella Putri Sihombing; Izwita Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study is the low level of students' understanding of mathematical concepts, especially in trigonometry, which requires innovation in learning. The inquiry learning model was chosen because it emphasizes student activities in discovering concepts through questioning, investigating, and proving, while Geogebra was used as an interactive medium to visualize mathematical concepts. This study aims to determine the effect of the Geogebra assisted inquiry learning model on the mathematical concept comprehension abilities of tenth-grade students. The research method used was a quasi-experiment with a one-group pretest-posttest design. The research sample consisted of 36 tenth-grade students selected through purposive sampling. The research instrument was a test of mathematical concept comprehension in the form of essay questions compiled based on four indicators, namely restating a concept, giving examples and non-examples of a concept, presenting concepts in mathematical representations, and applying a concept or problem-solving algorithm. The data were analyzed through validity, reliability, difficulty level, discriminating power, and normality tests. Hypothesis testing was conducted using a t-test with the help of SPSS software. Based on the t-test results, the average pretest score for students was 9.4722, while the average posttest score increased to 12.8611 after participating in learning with the GeoGebra-assisted inquiry model. Thus, there was a difference in the average increase of 3.3889 points, so was rejected and was accepted. This proves that there is an effect of media-assisted inquiry using Geogebra on the mathematical concept comprehension abilities of 10th grade students at SMA Negeri 1 Doloksanggul.